Reduction of selenite by bacterial exudates. (1st December 2022) - Sullivan, Leah C.; Boyanov, Maxim I.; Wright, Joshua T.; Warren, Mark C.; Kemner, Kenneth M.; Fein, Jeremy B.
Abstract: Bacterial reduction of Se(IV) is a significant component of the global selenium cycle, and hence affects the fate and transport of selenium in both natural and contaminated environments. However, it is unknown whether bacterially-produced exudates are capable of reducing selenium independent of bacterial cells. In this study, we measured the rate and extent of Se(IV) reduction by exudates from three bacterial species, and we determined the importance of exudate sulfhydryl sites by conducting parallel experiments after treatment of the exudates with a sulfhydryl-specific blocking molecule. We also conducted experiments with whole cell biomass for each of the three bacterial species to determine the importance of exudate-only reduction relative to whole biomass-promoted reduction. Under our experimental conditions, exudates from Bacillus subtilis and Pseudomonas putida remove Se(IV) from solution after an approximately 20–24 h lag period, but exudates from Shewanella oneidensis are ineffective at Se(IV) removal, except when the cells are grown in the presence of Se(IV). For both B. subtilis and P. putida, pretreatment blocking of the sulfhydryl sites on the exudate molecules dramatically decreases the rate and extent of Se(IV) removal, strongly suggesting that sulfhydryl groups on the exudate molecules play a key role in the Se(IV) reduction mechanism. The behavior of S. oneidensis exudates indicates that up-regulation of the Se(IV) reduction mechanism can occur in response to the Se content of the medium in which the cells grow. Our results demonstrate the capacity of some bacterial exudates to reduce Se(IV), and suggest that the activity of bacterial exudates should be accounted for when modeling selenium cycling in natural and engineered environments.